(untitled) (Mongolian Journal of Agricultural Sciences, 2024)
The genetic diversity of Mongolian native horse breeds Mongol, Galshar, Tes, and the lines Darkhad and Undurshil was studied using coat color gene and microsatellite marker polymorphism analyses. A total of 2,000 horses were characterized based on predominant coat color phenotypes and associated genes. Among six coat color genes, the highest average heterozygosity was observed in the Undurshil line, while the Tes breed exhibited the lowest. Microsatellite analysis of 17 markers in 259 horses identified 225 alleles, including 80 private alleles. ASB17 was the most polymorphic marker, whereas HTG4 was the least. The Galshar breed displayed the highest genetic diversity, with Na (10.4), Ne (0.795), No (0.726), and PIC (0.802) parameters, while the Darkhad line showed the lowest values. Principal coordinate analysis (PCoA) and cluster analysis revealed distinct genetic structures among the populations. The Darkhad line was notably different from other breeds, while the Galshar breed shared genetic similarities with the Undurshil line, and the Mongol breed was genetically similar to the Tes breed. These findings provide critical insights into the genetic diversity and population structure of Mongolian native horse breeds, supporting their conservation and sustainable management.